Where there is no morphine: The challenge and hope of palliative care delivery in Tanzania - Kristopher Hartwig; Mervyn Dean; Kari Hartwig; Paul Z. Mmbando; Abduraoof Sayed; Elma de Vries (AOSIS, 2014)
Background: In Tanzania, a country of 42 million, access to oral morphine is rare. Aim: To demonstrate the effectiveness of palliative care teams in reducing patients' pain and in increasing other positive life qualities in the absence of morphine; and to document the psychological burden experienced by their clinical providers, trained in morphine delivery, as they observed their patients suffering and in extreme pain. Setting: One hundred and forty-fie cancer patients were included from 13 rural hospitals spread across Tanzania. Method: A mixed method study beginning with a retrospective quantitative analysis of cancer patients who were administered the APCA African POS tool four times. Bivariate analyses of the scores at time one and four were compared across the domains. The qualitative arm included an analysis of interviews with six nurses, each with more than fie years' palliative care experience and no access to strong opioids. Results: Patients and their family caregivers identifid statistically signifiant (p < 0.001) improvements in all of the domains. Thematic analysis of nurse interviews described the patient and family benefis from palliative care but also their great distress when 'bad cases' arose who would likely benefi only from oral morphine. Conclusion: People living with chronic cancer-related pain who receive palliative care experience profound physical, spiritual and emotional benefis even without oral morphine. These results demonstrate the need for continued advocacy to increase the availability of oral morphine in these settings in addition to palliative care services.